How Slovak Economic Development (Did Not) Contributed To Its Employment Growth - Hudcovský, Martin; Fifeková, Elena (European Scientific Journal, ESJ, 2016)
The socio-economic development of Slovakia in past two decades is considered to be a success. One of few parameters where the development did not fully reflect is the unemployment rate. Despite the effort in this area, it is still lagging behind the other neighbouring countries. The paper provides some interesting insights how was the employment (and unemployment) affected by the economic development of the country. Based on structural decomposition, the two scenarios were created to simulate the possible outcome of economic development if certain parameters would remain stable over the time. The first scenario underlines the role of catching up process in the technological gap; the second scenario deals with the role of overall economy structure change.